Study the Temperature Effects on Mechanical Properties of Cold Cured Denture Base Acrylic Material - Enas G Younis (University of Mosul, College of Dentistry, 2013)
Aims: The purpose of this study is to explore the behavior of cold curing acrylic resin which used in dentistry during some mechanical properties (hardness, compression and impact)tests under different temperatures. Materials and Methods: Twenty four pinks from cold cured samples for each mechanical-physical properties tested were prepared under temperatures(20,24,28,32,37,45,50) C0 to cover a wide range similar to actual service temperatures. All specimens were soaked in distilled water. One hour ,two hours ,three hours were chosen as the time for soaking and the means of the tests were recorded. Results: The results show that the compression and hardness decreasing with the increasing of temperature and increase of impact strength with the increase of temperature up to (28) C0 then followed by a decrease in impact strength. Conclusions: The decrease of compressive strength and hardness is compatible with the results obtained under compressive Conditions. Keywords: Temperature, mechanical properties, cold cured material.